Rushdi Gaafar - A Yemeni with the flair for Malay language - Mohd Ferdaus, Musa (2018)
Yemeni Rushdi Gaafar Ahmed Baragaa was picked to represent Universiti Malaysia Pahang (UMP) in the International Malay Language Debate Competition (PABM) that was held at Universiti Sultan Zainal Abidin (UniSZA) in Terengganu on December 20, 2018.